1996
DOI: 10.1080/02688699650040133
|View full text |Cite
|
Sign up to set email alerts
|

Value of visual evoked potential monitoring during trans-sphenoidal pituitary surgery

Abstract: The visual outcome of 22 patients undergoing trans-sphenoidal excision of pituitary macroadenomas with intraoperative flash visual evoked potential (VEP) monitoring (Group A), was compared with a non-randomized group of 14 patients who had undergone similar operations without VEP monitoring (Group B). Tumour size, preoperative visual acuity, peripheral fields, and latencies and amplitudes of P1 and P2 were analysed to ascertain the best predictor of postoperative visual function. It was found that patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Patients with pituitary tumors offer a new model for understanding both the process of spontaneous remyelination in the human brain and the functional consequences of that remyelination, and therefore, provide new leverage on the development of biomarkers for secondary white matter injury. This is significant, because as noted above, there have been notable failures to predict the likelihood of visual recovery following decompression of retinofugal nerves: factors such as tumor size, duration of compression, severity of pre-surgical visual impairments, and age do not predict visual outcome (10-12). Previous neuro-ophthalmologic research on macroadenoma patients (15, 37) using pattern electroretinography (PERG), photopic negative response (PhNR) and retinal nerve fiber layer (RNFL) thickness has found that PERG is able to predict only failure of visual recovery (38), whereas post-operative PhNR and RNFL thickness significantly correlate with visual field outcomes at three to six months (15).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pituitary tumors offer a new model for understanding both the process of spontaneous remyelination in the human brain and the functional consequences of that remyelination, and therefore, provide new leverage on the development of biomarkers for secondary white matter injury. This is significant, because as noted above, there have been notable failures to predict the likelihood of visual recovery following decompression of retinofugal nerves: factors such as tumor size, duration of compression, severity of pre-surgical visual impairments, and age do not predict visual outcome (10-12). Previous neuro-ophthalmologic research on macroadenoma patients (15, 37) using pattern electroretinography (PERG), photopic negative response (PhNR) and retinal nerve fiber layer (RNFL) thickness has found that PERG is able to predict only failure of visual recovery (38), whereas post-operative PhNR and RNFL thickness significantly correlate with visual field outcomes at three to six months (15).…”
Section: Discussionmentioning
confidence: 99%
“…While some authors only see very limited use of VEP-monitoring under surgery at all [4][5][6][7][8], others have published optimistic results [9][10][11][12][13]. There is agreement on the need of further improvement regarding stimulation characteristics, recording technique, and anesthesiological management.…”
Section: Introductionmentioning
confidence: 94%
“…There were four studies that reported statistical data only regarding severity of vision loss. Two reported no significant association 50,69 and two reported significant association. One of these showed r ¼ 0.656 (p < 0.001), 13 and the other described a "significant correlation" 49 with no further description of the analysis.…”
mentioning
confidence: 91%